2012
DOI: 10.1177/1753193412469898
|View full text |Cite
|
Sign up to set email alerts
|

Proximal interphalangeal joint replacement with an unconstrained pyrocarbon prosthesis (Ascension®): a long-term follow-up

Abstract: There have been limited publications that report long-term outcomes of pyrocarbon implants. This report describes both clinical and radiographic long-term results for patients who have been treated with pyrocarbon proximal interphalangeal implants. Thirteen implants in ten patients are reported for an average follow-up of 8.3 years (range 6.2-9.3). All patients were suffering from degenerative joint disease. Five of the 13 digits were free of pain, the remaining eight digits had mild to moderate pain (visual a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Moreover, the revision incidence seems higher for surface gliding implants compared to silicone arthroplasty. 15,32,39 Daecke et al 33 reported a revision incidence of 11% for silicone spacers, 27% for titanium devices, and 39% for pyrocarbon prostheses after a mean follow-up of 35 months. Pritsch and Rizzo 15 confirmed this observation and found that the number of reoperations per finger for pyrocarbon prostheses and metal-plastic surface replacement was 1.5 and 1.8 respectively, although the majority of secondary surgeries were done for soft tissue complications.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the revision incidence seems higher for surface gliding implants compared to silicone arthroplasty. 15,32,39 Daecke et al 33 reported a revision incidence of 11% for silicone spacers, 27% for titanium devices, and 39% for pyrocarbon prostheses after a mean follow-up of 35 months. Pritsch and Rizzo 15 confirmed this observation and found that the number of reoperations per finger for pyrocarbon prostheses and metal-plastic surface replacement was 1.5 and 1.8 respectively, although the majority of secondary surgeries were done for soft tissue complications.…”
Section: Discussionmentioning
confidence: 97%
“…3 Proximal interphalangeal arthroplasty has consistently produced satisfactory pain relief and increased joint mobility for most patie nts. 8,[15][16][17][18][19][20][21][22][23][24][25][26][27] It was once a mainstay treatment for RA, but with the introduction of disease-modifying antirheumatic drugs in the 1990s, the need for PIPA in this patient population has continually decreased in the recent decades. Nonetheless, reconstruction rates for the osteoarthritic hand have gradually increased.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient detail was provided on the exercise programmes, primarily with regards to the intensity and frequency of the exercises ( Table 2). Studies that did provide some guidelines were considerably vague, for example "unrestricted grip activities" (9) or "light, controlled activities" [10]. As there is a risk of further damaging a joint by exercising at an inappropriate intensity [11], studies should ensure sufficient detail is provided to enable the reader to fully understand the specific treatment that was implemented to replicate in practice.…”
Section: Methodsmentioning
confidence: 99%